Opportunity or Burden? A Behavioral Framework for Patient Engagement. Issue 2 (February 2020) - Kimerling, Rachel; Lewis, Eleanor T.; Javier, Sarah J.; Zulman, Donna M.
Abstract : Background: Engaging patients as partners in their care is clinically appealing, yet challenging to implement, and we lack a measurement framework that is applicable to vulnerable populations. To address this gap, we conducted a qualitative study to refine a conceptual framework that reflects an individual's propensity to engage with care. Objectives: Our objectives were to refine the framework's domains of engagement behavior; identify key behaviors within each domain that describe engagement with providers, health systems or settings; and illustrate examples for each behavior where higher self-efficacy describes an opportunity to enhance engagement, and lower self-efficacy describes difficulties with engagement that risk burden. Research Design and Sample: We elicited patient perspectives by conducting individual semistructured interviews with veterans receiving care for mental health and/or chronic conditions from the Veterans Health Administration. Data were analyzed using the framework method. Results: The resulting engagement framework encompassed 4 interrelated domains: Self-Management, Health Information Use, Collaborative Communication, and Healthcare Navigation. The propensity to engage with care was conceptualized as the cumulative self-efficacy to engage in behaviors across these domains. Results emphasize the collaborative nature of engagement behaviors and the impact of veteran cultural influences via perceptions of collective efficacy. Conclusions: This framework can be applied to judgments regarding a patient's propensity to engage in care. Because self-efficacy is an individual's context-specific judgment of their capabilities, this framework may inform health care and social service interventions that aim to engage patients. This maybe especially useful for public sector settings and populations with social risks. Abstract : Supplemental Digital Content is available in the text.